PENINGKATAN KOMPETENSI GURU MENUJU ERA REVOLUSI INDUSTRI 5.0 - Royani, Ida (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The issue of teachers will be increasingly complex entering the era of the Industrial Revolution 5.0, where teachers must have competence in facing technological developments. This paper examines efforts to improve teacher competency towards the era of the Industrial Revolution 5.0. Efforts to improve teacher competency are carried out by improving teacher recruitment systems, bottom up patterns of teacher competency improvement, Empowerment of Teacher Activity Groups and Subject Teachers' Deliberations to create a collaboration oriented to teacher self-development, and optimization of Sustainable Professional Improvement programs and lesson study with e-literacy support. The Indonesian Parliament in carrying out the legislative function, can provide support in the form of a commitment to accelerate the preparation of the Draft Law on Teachers. Need special attention in formulating the substance regarding teacher competence. Keywords— Teacher competence, The industrial revolution 5.0 Abstrak— Persoalan guru akan semakin kompleks memasuki era Revolusi Industri 5.0, di mana guru harusmempunyai kompetensi dalam menghadapi perkembangan teknologi dan softskill. Tulisan ini mengkaji upaya peningkatan kompetensi guru menuju era Revolusi Industri 5.0. Upaya peningkatan kompetensi guru dilakukan dengan perbaikan sistem rekrutmen guru,polapeningkatankompetensiguruyangbersifatbottomup,pemberdayaan Kelompok Kegiatan Guru dan Musyawarah Guru Mata Pelajaran untuk menciptakan suatu kolaborasi yang berorientasi pada pengembangan diri guru, dan optimalisasi program Peningkatan Keprofesian Berkelanjutan dan lesson study dengan dukungan e-literasi. DPR RI dalam menjalankan fungsi legislasi, dapat memberikan dukungan berupa komitmen untuk mempercepat penyusunan Rancangan Undang-Undang tentang Guru. Perlu perhatian khusus dalam merumuskan substansi mengenai kompetensi guru. Kata Kunci— kompetensi guru, revolusi industri 5,0